The Effect of Service Quality and Brand Trust on Customer Satisfaction at PO Manggala - Orlando, Gerry Hutama; Ugy Soebiantoro (Fakultas Ekonomi & Bisnis Universitas Muslim Indonesia, 2025)
This study will look into how service quality and brand trust affect customer satisfaction at PO Menggala in Surabaya. A quantitative research design was utilized, employing a survey method via an online questionnaire. The study adopted purposive sampling, involving 99 respondents who had previously utilized the services of PO Menggala. Data were analyzed using the Partial Least Squares Structural Equation Modeling (PLS-SEM) technique with the support of SmartPLS software. The findings reveal that both service quality and brand trust exert a positive and significant influence on customer satisfaction. These results suggest that consistent service performance and established brand trust are critical determinants of customer satisfaction. Accordingly, it is recommended that PO Menggala sustain high service quality and reinforce its brand image to foster long-term customer loyalty.